WHO collaborative registration procedure using stringent regulatory authorities' medicine evaluation: reliance in action?. Issue 1 (2nd January 2022) - Vaz, Alexandra; Roldão Santos, Mariana; Gwaza, Luther; Mezquita González, Elena; Pajewska Lewandowska, Magdalena; Azatyan, Samvel; Saint-Raymond, Agnès
ABSTRACT: Introduction: The regulatory approval of medical products in countries with limited regulatory resources can be lengthy, which often compromises patients' timely access to much-needed medicines. To improve the efficiency of regulatory systems, reliance is being used. Reliance allows an authority to leverage the work performed by other authorities, such as scientific evaluations, to decide on medical products approval within their jurisdiction. This reduces duplication of regulatory efforts, resources and time, while maintaining national sovereignty. Areas covered: This article analyzes the outcomes and stakeholders' experience of using medicines assessments performed by Stringent Regulatory Authorities (SRA) in the Collaborative Registration Procedures (CRP). Since its establishment in 2015, 59 approvals were granted to 16 medicines in 23 countries through SRA CRP. Results show that the procedure is delivering on the intended benefits of access and speed, with long-term positive impact for resource-limited countries. The article concludes with recommendations on the need for guidance on management of post-approval changes, wider promotion of the procedure, and increased collaboration between authorities. Expert opinion: The SRA CRP provides a mechanism for the use of reliance by strengthening communication and promoting the exchange of information among regulators. This fosters faster regulatory approvals and, consequently, earlier access to medicines.